Militarização, política criminal de drogas e tortura: estratégias práticas e discursivas de controle no Rio de Janeiro - Bezerra, Ana Carolina Carneiro Barde (2021)
In Rio de Janeiro, young men from Complexo da Penha were arrested by army forces after a police operation which was endorsed by the state's public security to combat drug trafficking. As a result, in addition to the arrests, people from the community were killed and narcotic and weapons were aprehended. The young men arrested on that date reported having been tortured inside the official room of the military forces. The Judiciary, when analyzing the case that became known as the 'Red Room' case, recognized the violence against the young men and ordered an investigation. Neverthelerss, it fails to follow the guidelines of the Human Rights Treaties on Torture, and the Istanbul Protocol, by not recognizing the illegality of the evidence obtained on that date, under the argument that the torture had not taken place at the time of the arrests, but only after the flagrant act. Through this case, this work intended to analyze in an abstract way forms of social control of the young population living in slums, belonging to economically underlying classes and mostly black. In this case, the confrontation against drug trafficking, militarization, torture, and the Judiciary, with greater focus on the penal system, all under the lens of the State of Rio Janeiro. The drug issue was analyzed from a global perspective to a Latin American perspective, focusing on racism, incarceration and genocide of bodies in situations of vulnerability. Militarization brings the historical perspective back from colonisation, passing through the dictatorial period, to the present time, with the nuances of Rio de Janeiro, such as the federal intervention, the Police Pacification Units and the militias. It also seeked to confront torture as a form of social control since Antiquity, when legal and accepted by different forms of State, passing to the national perspective regarding the civil-military dictatorship and its racist and slavery contours. Finally, it was brought the perspective of the Judiciary Branch of Rio de Janeiro on cases related to the theme, on the analysis of the resistance acts, when there is lethality of peripheral bodies by the police in confrontation for the repression of drug trafficking. Two other Rio cases analyzed by the Inter-American Court of Human Rights were also addressed, dealing with police lethality and imprisonment, demonstrating the bureaucratic judicial machine that seals the forms of control presented in this dissertation